Theory of room temperature ferromagnetism in Cr modified DNA nanowire - DEĞER, CANER; AKTAŞ, ŞAHİN (IOP PUBLISHING LTD, 2016)
We investigated the magnetic properties of Cr3+ (J < 0) ion-modified DNA (M-DNA) nanowire (1000 base) at room temperature under a uniform magnetic field (similar to 100 Oe) for different doping concentrations. A Monte Carlo simulation method-based Metropolis algorithm is used to figure out the thermodynamic quantities of nanowire formed by Cr M-DNA followed by analysing the dependency of the ferromagnetic behaviour of the M-DNA to dopant concentration. It is understood that ion density/base and ion density/helical of Cr3+ ions can be a tuning parameter, herewith the dopant ratio has an actual importance on the magnetic characterization of M-DNA nanowire (3%-20%). We propose the source of magnetism as an exchange interaction between Cr and DNA helical atoms indicated in the Heisenberg Hamiltonian.
Keywords: organic nanowires; modified DNA (m-DNA); Monte Carlo method; Heisenberg Hamiltonian; MAGNETIC-PROPERTIES; STATE